2014
DOI: 10.1371/journal.pone.0103001
|View full text |Cite
|
Sign up to set email alerts
|

Road Traffic Deaths and Injuries Are Under-Reported in Ethiopia: A Capture-Recapture Method

Abstract: In low and middle income countries road traffic injuries are commonly under-reported. This problem is significantly higher among those less severely injured road users. The objective of this study was to determine the incidence and the level of ascertainment of road traffic injuries and deaths by traffic police and hospital registry. In this study two-sample capture-recapture method was applied using data from traffic police and hospital injury surveillance, through June 2012 to May 2013. The study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 24 publications
1
58
2
2
Order By: Relevance
“…Although alcohol positive, speeding and poor light conditions have been associated with increased risk of injury severity in studies performed in Ethiopia and Kenya 23,27 , these factors were not associated with increased risk of grievous injury in this study. The reasons for this discrepancy are not clear, but could be a reflect of the overall lack of infra-structure of Tanzanian roads and the reporting method, which makes it harder to identify alcohol use, time of crash or driving behavior.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Although alcohol positive, speeding and poor light conditions have been associated with increased risk of injury severity in studies performed in Ethiopia and Kenya 23,27 , these factors were not associated with increased risk of grievous injury in this study. The reasons for this discrepancy are not clear, but could be a reflect of the overall lack of infra-structure of Tanzanian roads and the reporting method, which makes it harder to identify alcohol use, time of crash or driving behavior.…”
Section: Discussioncontrasting
confidence: 60%
“…It is uncertain whether missing data were truly non-random. Previous studies have shown under-reporting of RTIs to police in low and middle income countries 27,35 , but to date there have been no quality assessments of the Moshi, Tanzania police data. Similarly, completeness of the police data was a challenge.…”
Section: Discussionmentioning
confidence: 97%
“…21 This means that there are no reliable baseline data that can be used to monitor the implementation of measures aimed at reducing RTIs and to monitor the coverage of pre-hospital and hospital care for RTI victims.…”
Section: Public Health Action Rtis In Addis Ababa Ethiopia 70mentioning
confidence: 99%
“…In such countries, CRVS data is frequently incomplete and/or include large numbers of deaths attributed to unknown causes . Other data sources on injuries and accidents include police reports and hospital records, but both sources are affected by under-reporting (Abegaz et al 2014;Sanghavi, Bhalla, and Das 2009;Sango et al 2016). For example, large numbers of accident victims may never be transported to a hospital.…”
Section: Introductionmentioning
confidence: 99%